Noodle making machine / Azril Firdaus Azmi - Azmi, Azril Firdaus (2022)
Noodles are a high demand food item required in a variety of dishes including chowmein, hakka noodles and a variety of dishes. Preparation of noodles from batter is a tiring process and difficult to be done by hand. Depend on the high demand the supply of noodles requires a tireless process to keep up with the huge demand. The process is tired so that the people stop from doing it. The main objectives of this project is to design and fabricate the noodle making machine that help people to create their own noodle and can cut more noodle with a short time. The methodologies that are used are preparing 3 design sketch and choose the best out of 3. Then, make engineering calculation with the dimensions selected and draw project in solidworks to make engineering analysis. The cost is calculated . Project expected to be a nice machine and can help to make a noodle